Exploring EEG Effective Connectivity Network in Estimating Influence of Color on Emotion and Memory - Chai, Meei Tyng; Amin, Hafeez Ullah; Izhar, Lila Iznita; Saad, Mohamad Naufal Mohamad; Abdul Rahman, Mohammad; Malik, Aamir Saeed; Tang, Tong Boon (Frontiers in Neuroinformatics, 2019)
Color is a perceptual stimulus that has a significant impact on improving human emotion and memory. Studies have revealed that colored multimedia learning materials (MLMs) have a positive effect on learner’s emotion and learning where it was assessed by subjective/objective measurements. This study aimed to quantitatively assess the influences of colored MLMs on emotion, cognitive processes during learning and long-term memory (LTM) retention using electroencephalography (EEG). The dataset consisted of 45 healthy participants, and MLMs were designed in colored or achromatic illustrations to elicit emotion and that to assess its impact on LTM retention after 30-minutes and 1-month delay. The EEG signal analysis was first started to estimate the effective connectivity network (ECN) using phase slope index and expand it to characterize the ECN pattern using graph theoretical analysis. EEG results showed that colored MLMs had influences on theta and alpha networks, including (1) an increased frontal-parietal connectivity (top-down processing), (2) a larger number of brain hubs, (3) a lower clustering coefficient, and (4) a higher local efficiency, indicating that color influences information processing in the brain as reflected by ECN together with a significant improvement in learner’s emotion and memory performance. This is evidenced by a more positive emotional valence and higher recall accuracy for groups who learned with colored MLMs than that of achromatic MLMs. In conclusion, this paper demonstrated how the EEG ECN parameters could help quantify the influences of colored MLMs on emotion and cognitive processes during learning.